Empowering the Role of the Integrated Foster Post Cadres in Improving the Quality of Life of Diabetes Mellitus Patients - Fitri Firranda Nurmalisyah; Alik Septian Mubarok; Desy Siswi Anjar Sari (Babali Health, 2021)
Introduction: Nurses as one of the health workers have a role in managing Diabetes Mellitus patients, the quality life of Diabetes Mellitus patients affects physical health, psychological conditions, level of dependence, social relations and the patient's relationship with the surrounding environment. Actions and interventions in controlling Diabetes Mellitus disease require appropriate therapeutic regimens, as well as involving families. By empowering the health cadres, it can improve the quality life of people with Diabetes Mellitus who are in the working area of the Kesamben Health Center, Jombang Regency. Methods: This research is a quasi-experimental study with a non-randomized control group pre-test post- test design. In this study, the treatment group was given a treatment in the form of training for Integrated Foster Post Cadres to improve for Diabetes Mellitus, while the control group was not given any treatment. Results: The results showed that there was a significant difference in the quality of life between the treatment group and the control group due to skills improvement training for Integrated Foster Post Cadres Diabetes Mellitus with the results of the independent t test on self-efficacy obtained t value of 25.055 (p = 0.000), while the value t of quality life is 25,790 (p = 0,000). Conclusion: Nurses can empower Integrated Foster Post Cadres in the community by improving the quality of life for people with Diabetes Mellitus. Integrated Foster Post Cadres play an active role in the community in the scope of knowledge, signs and symptoms, complications of Diabetes Mellitus which can encourage DM sufferers to be motivated to improve the quality of life.